Single cell oil production using Lipomyces starkeyi : fermentation, lipid analysis and use of renewable hemicellulose-rich feedstocks - Probst, Kyle V. (Kansas State University, 2014)
As the world population continues to grow and the uncertainty of petroleum and food availability transpires, alternative resources will be needed to meet our demands. Single cell oil (SCO) from oleaginous yeast is a renewable noncrop-based resource that can be used for the production of petroleum counterparts. Currently, commercial production is limited, mainly due to high production costs and competition from cheaper alternatives. As a result, improved fermentation techniques, utilization of low-valued feedstocks and efficient downstream processing would be highly valuable. The major objectives of this study were to: 1) optimize fermentation conditions for the development of a novel fed-batch fermentation to enhance oil production using Lipomyces starkeyi, 2) determine the major lipids produced by L. starkeyi, 3) utilize low-valued hemicellulose-rich feedstocks for oil production, and 4) demonstrate the use of 2-methyltetrahydrofuran (2-MeTHF) and cyclopentyl methyl ether (CPME) as greener solvents for oil extraction. Under optimized fermentation conditions, the oil yield increased from 78 to 157 mg oil/g sugar when supplying xylose rather than glucose as the major carbon source. A novel repeated fed-batch fermentation supplying glucose for growth and xylose for lipid accumulation generated the highest oil yield of 171 mg oil/g sugar, oil content of 60% (dry mass basis) and oil productivity of 143 mg oil/L/hr. Oleic acid accounted for 70% of the total fatty acid profile indicating that oil from L. starkeyi is a naturally high source of oleic acid; an added benefit for the biofuel, cosmetic, food, and oleochemical industries. Hemicellulose-rich corn bran and wheat bran were successfully used to produce oil; oil yields of 125 and 71 mg oil/g sugar were reported for whole and de-starched bran hydrolysates, respectively. Compared to traditional methods, biphasic oil extraction systems of 2-MeTHF and CPME had an 80 and 53% extraction efficiency and 64 and 49% selectivity, respectively. The information from this study will be useful for the development of an integrated approach to improve the viability of SCO biochemical platforms for the production of advanced biofuels and renewable chemicals.
Keywords: Oleaginous yeast; Bioprocessing; Single cell oil; Hemicellulose; Value-addition; Lipid extraction; Agriculture, General (0473); Chemical Engineering (0542); Microbiology (0410)